Teacher job satisfaction by principal support and teacher cooperation: Results from the Schools and Staffing Survey - Amanda Olsen; Francis Huang (Arizona State University, 2019)
Although turnover rates are alarmingly high for early career and veteran teachers, turnover rates are even higher for those who identify as a teacher of color. To increase the retention of teachers, job satisfaction has become an important construct to analyze. Teacher cooperation and principal support within the school are two influential factors that directly relate to job satisfaction. Using the restricted 2011-2012 Schools and Staffing Survey, a nationally representative dataset, principal support, teacher cooperation, and their moderation effects were analyzed in relation to teacher job satisfaction using a series of multilevel models. After controlling for teacher- and school-level characteristics, principal support and teacher cooperation were statistically significant predictors of job satisfaction for all teachers. The moderation effect between the two variables of interest and race were also statistically significant. These findings emphasize the need to maintain professional communities where teachers can interact and collaborate with the support of their school leaders.